The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2478/squa-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic Position of Tills in the Orłowo Cliff Section (Northern Poland): A New Approach

Abstract: The site at Orłowo Cliff was used to analyse the stratigraphic position and palaeogeographic interpretations of the properties and depositional conditions of two basal tills from the Late Pleistocene. A multi-proxy approach involved lithofacies, petrographic analysis of the fine gravel fraction, analyses of indicator erratics and till fabric. TL dating of intra-moraine deposits was used to determine depositional time frames of tills. The sediment profile at Orłowo Cliff shows a distinct reduction in number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(31 reference statements)
2
7
0
Order By: Relevance
“…Gross (1933Gross ( , 1942, likewise, stated that the rocks of the Old Red Sandstone in which he and Kade found scales of Porolepis posnaniensis had to be transported from the area of Estonia. This agrees with the putative transport direction of the ice flow from a northeastern source area that comprises the region between St. Petersburg and northern Lithuania (Wozńiak et al, 2018). Well-preserved vertebrate material has been described from Latvia (e.g., Hajłasz, 1974;Märss, 1986;Bjerkéus, 2001), which probably was the source area for boulders that occur in postglacial material in Poland.…”
Section: Geological Settingsupporting
confidence: 79%
See 1 more Smart Citation
“…Gross (1933Gross ( , 1942, likewise, stated that the rocks of the Old Red Sandstone in which he and Kade found scales of Porolepis posnaniensis had to be transported from the area of Estonia. This agrees with the putative transport direction of the ice flow from a northeastern source area that comprises the region between St. Petersburg and northern Lithuania (Wozńiak et al, 2018). Well-preserved vertebrate material has been described from Latvia (e.g., Hajłasz, 1974;Märss, 1986;Bjerkéus, 2001), which probably was the source area for boulders that occur in postglacial material in Poland.…”
Section: Geological Settingsupporting
confidence: 79%
“…These boulders were reworked by recent sea-wave activity; therefore, the exact position in the profile is difficult to determine. However, the occurrence of the 'Old Red Sandstone' erratics within the 0-4 unit was noted by Wozńiak et al (2018), who identified the potential source area as Lithuania (Wozńiak et al, 2018:fig. 4c).…”
Section: Geological Settingmentioning
confidence: 99%
“…There are two main lithostratigraphic units in the research area. The older unit is composed of fine sands, silts, and lignite of the Neogene (Pikies 2001;Pikies andZaleszkiewicz 2004, 2013a, b;Woźniak et al 2018). These deposits are only exposed in cliffs.…”
Section: Study Areamentioning
confidence: 99%
“…These deposits are only exposed in cliffs. The younger unit consists of glacial tills, fluvioglacial sands, and gravels, along with limnoglacial silts and clays of Pleistocene as well as Holocene fluvial sands, muds, and peat (Pikies 2001;Pikies andZaleszkiewicz 2004, 2013a, b;Woźniak et al 2009Woźniak et al , 2018Woźniak and Czubla 2016). Holocene alluvial and colluvial deposits occur along the valley bottoms.…”
Section: Study Areamentioning
confidence: 99%
“…In Europe, both the last and earlier Pleistocene glaciations have been studied in this regard [10,16,[25][26][27][28][29][30][31]. Indicator and auxiliary erratics found in Poland have also been described, and their source areas have been identified [29,[32][33][34][35][36][37][38]. Recently, research has focused on the Middle Polish Glaciation-Odranian/Wartanian (Saalian, Marine Oxygen-Isotope Stage (MIS) 6) [33, [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%